Incentivizing Around the Globe: Educating for the Challenge of Developing Culturally Considerate Work Motivation Strategies. (September 2017) - Mills, Maura J.
Work motivation has long been considered a driving force behind optimal employee management. However, as the workscape continues its path toward increased globalization, today's managers must consider cultural influences on employee motivation to implement the most appropriate human capital management strategies within any given context. The classroom exercise described herein challenges students to do just that. This exercise allows students to consider how employees' culture may interact with their motivations in specific job-relevant contexts, challenging them to develop a culturally considerate motivation plan to drive their employees toward an organizationally desired outcome. As such, the exercise is appropriate for a variety of courses (e.g., Human Resource Management, Work Motivation, Organizational Behavior) at both undergraduate and graduate levels, and options are presented at each stage of the exercise that may be in/excluded at the discretion of the instructor depending on course level and focus.